La pintura mural como medio artistico y simbolico sobre el abandono animal en el canton pasaje - Armijos Ramon, Jonathan Manuel (Machala, 2025)
The present research document in Plastic Arts entitled “Mural painting as an artistic and symbolic medium on animal abandonment in the Pasaje Canton” addresses a social problem of great relevance: animal abandonment. This situation affects not only citizen coexistence, but also the balance of the urban and natural environment. The main objective of the research is the creation of a mural that serves as a point of reflection, promoting changes in perception and generating spaces for education and values that foster respect and affection towards animals. Muralism has been throughout history a means of visual expression that not only beautifies public spaces, but also communicates messages of a social, political and cultural nature. Artists from different parts of the world have used mural art to denounce injustices, transmit values and inspire changes in society. In the context of animal abandonment, pictorial representation in murals can serve as a powerful tool to raise awareness among the population about the responsibility that coexistence with animals entails. The study prior to the creation of the mural included a review of various urban artists and activists who have addressed similar issues in their works. An analysis was made of how images can generate empathy and awareness in the viewer. The selection of images and compositions was guided by a symbolic and sentimental approach, seeking to emotionally connect with the community and awaken a deep reflection on the situation of abandoned animals. The abandonment of animals is a problem that not only affects the animals themselves, but also has repercussions on urbanization and tourism in the city. In many cities around the world, the presence of street animals generates a negative impact on the urban image, which can influence economic development and the perception of visitors. However, beyond the visual impact, the abandonment of animals reflects a lack of empathy and values in society. In the study carried out, works were identified that adopt a radical stance to denounce the mistreatment and exploitation of animals in various forms, such as cockfights, bullfights and dogfights. These practices respond to economic and cultural interests that perpetuate animal suffering under the justification of entertainment and tradition. One of the aspects that the mural seeks to highlight is the social differentiation that also exists in the animal world. The comparison between a stray dog and a purebred dog that enjoys all the comforts is a clear example of how animals also suffer inequalities depending on their origin and condition. This visual representation aims to generate a debate in the community about the different treatment that animals receive and the importance of promoting responsible adoption instead of indiscriminate purchase. The mural not only seeks to be an aesthetically attractive work, but also a space for dialogue and reflection on animal abandonment. Through striking images and clear messages, it is hoped that the public will be able to question their own actions and decisions regarding animal ownership. In addition, it is intended to raise awareness about the importance of sterilization, responsible care and respect for all forms of life. In conclusion, muralism is presented as an artistic and symbolic tool of great impact to address social problems such as animal abandonment. Through this research and the creation of a mural in Cantón Pasaje, we seek to generate a change in the perception of the community, promoting values of empathy and responsibility towards animals. The mural will not only be a visual testimony of social reality, but also a starting point for education and collective action in favor of animal welfare.
El presente documento de investigación en Artes Plásticas titulado “La pintura mural como medio artístico y simbólico sobre el abandono animal en el Cantón Pasaje” aborda una problemática social de gran relevancia: el abandono animal. Esta situación afecta no solo la convivencia ciudadana, sino también el equilibrio del medio ambiente urbano y natural. El objetivo principal de la investigación es la creación de un mural que sirva como un punto de reflexión, promoviendo cambios de percepción y generando espacios de educación y valores que fomenten el respeto y el afecto hacia los animales. El muralismo ha sido a lo largo de la historia un medio de expresión visual que no solo embellece espacios públicos, sino que también comunica mensajes de carácter social, político y cultural. Artistas de diferentes partes del mundo han utilizado el arte mural para denunciar injusticias, transmitir valores e inspirar cambios en la sociedad. En el contexto del abandono animal, la representación pictórica en murales puede servir como una herramienta poderosa para sensibilizar a la población sobre la responsabilidad que implica la convivencia con los animales. El estudio previo a la elaboración del mural incluyó la revisión de diversos artistas urbanos y activistas que han abordado problemáticas similares en sus obras. Se analizó cómo las imágenes pueden generar empatía y conciencia en el espectador. La selección de imágenes y composiciones estuvo guiada por un enfoque simbólico y sentimental, buscando conectar emocionalmente con la comunidad y despertar una reflexión profunda sobre la situación de los animales abandonados. El abandono de animales es una problemática que no solo afecta a los propios animales, sino que también tiene repercusiones en la urbanización y el turismo de la ciudad. En muchas ciudades del mundo, la presencia de animales en situación de calle genera un impacto negativo en la imagen urbana, lo que puede influir en el desarrollo económico y la percepción de los visitantes. Sin embargo, más allá del impacto visual, el abandono de animales refleja una falta de empatía y valores en la sociedad. En el estudio realizado, se identificaron obras que adoptan una postura radical para denunciar el maltrato y la explotación de los animales en diversas formas, como las peleas de gallos, corridas de toros y peleas de perros. Estas prácticas responden a intereses económicos y culturales que perpetúan el sufrimiento animal bajo la justificación del entretenimiento y la tradición. Uno de los aspectos que el mural busca resaltar es la diferenciación social que también existe en el mundo animal. La comparación entre un perro callejero y un perro de raza que goza de todas las comodidades es un ejemplo claro de cómo los animales también sufren desigualdades dependiendo de su origen y condición. Esta representación visual pretende generar un debate en la comunidad sobre el trato diferenciado que reciben los animales y la importancia de promover la adopción responsable en lugar de la compra indiscriminada. El mural no solo busca ser una obra estéticamente atractiva, sino también un espacio de diálogo y reflexión sobre el abandono animal. A través de imágenes impactantes y mensajes claros, se espera que el público pueda cuestionar sus propias acciones y decisiones respecto a la tenencia de animales. Además, se pretende generar conciencia sobre la importancia de la esterilización, el cuidado responsable y el respeto hacia todas las formas de vida. En conclusión, el muralismo se presenta como una herramienta artística y simbólica de gran impacto para abordar problemáticas sociales como el abandono animal. A través de esta investigación y de la creación de un mural en el Cantón Pasaje, se busca generar un cambio en la percepción de la comunidad, fomentando valores de empatía y responsabilidad hacia los animales. La obra mural no solo será un testimonio visual de la realidad social, sino también un punto de partida para la educación y la acción colectiva en pro del bienestar animal.
Keywords: ABANDONO ANIMAL; ARTE URBANO MURAL; HISTORIA DEL ARTE; CRITICA DEL ARTE; ARTE Y ACTIVISMO